Bioactive Electrospun Fibers of Poly(glycerol sebacate) and Poly(ε‐caprolactone) for Cardiac Patch Application. Issue 13 (13th August 2015) - Rai, Ranjana; Tallawi, Marwa; Frati, Caterina; Falco, Angela; Gervasi, Andrea; Quaini, Federico; Roether, Judith A.; Hochburger, Tobias; Schubert, Dirk W.; Seik, Lothar; Barbani, Niccoletta; Lazzeri, Luigi; et al.
Abstract : Scaffolds for cardiac patch application must meet stringent requirements such as biocompatibility, biodegradability, and facilitate vascularization in the engineered tissue. Here, a bioactive, biocompatible, and biodegradable electrospun scaffold of poly(glycerol sebacate)–poly(ε‐caprolactone) (PGS–PCL) is proposed as a potential scaffold for cardiac patch application. The fibers are smooth bead free with average diameter = 0.8 ± 0.3 μm, mean pore size = 2.2 ± 1.2 μm, porosity = 62 ± 4%, and permeability higher than that of control biological tissue. For the first time, bioactive PGS–PCL fibers functionalized with vascular endothelial growth factor (VEGF) are developed, the approach used being chemical modification of the PGS–PCL fibers followed by subsequent binding of VEGF via amide bonding. The approach results in uniform immobilization of VEGF on the fibers; the concentrations are 1.0 μg cm −2 for the PGS–PCL (H) and 0.60 μg cm −2 for the PGS–PCL (L) samples. The bioactive scaffold supports the attachment and growth of seeded myogenic and vasculogenic cell lines. In fact, rat aortic endothelial cells also display angiogenic features indicating potential for the formation of vascular tree in the scaffold. These results therefore demonstrate the prospects of VEGF‐functionalized PGS–PCL fibrous scaffold as promising matrix for cardiac patch application. Abstract : A bioactive, biocompatible, and biodegradable electrospun scaffold of poly(glycerol sebacate)‐poly(ε‐caprolactone) (PGS–PCL) functionalized with vascular endothelial growth factor (VEGF) supports attachment and growth of myogenic and vasculogenic cell lines. These PGS–PCL (VEGF) fibers are a promising matrix for cardiac patch application.